In: Chemistry
2. Consider the equilibria shown below:
Pb3(PO4)2(s)→← 3 Pb2+(aq) + 2 PO43-(aq) Keq = 1.0 x 10-54
Pb2+(aq) + 3 OH-(aq)→← Pb(OH)3-(aq) Keq = 8.0 x 1013
Pb3(PO4)2(s) + 9 OH-(aq)→← 3 Pb(OH)3-(aq) + 2 PO43-(aq)
a) Calculate the equilibrium constant for the third equilibrium shown.
b) Calculate the equilibrium concentrations of Pb(OH)3- and of PO43- in a pH 10 solution containing the third equilibrium.
we need to:
multiply rxn 2 by 3
Pb3(PO4)2(s) →← 3 Pb2+(aq) + 2 PO43-(aq) Keq = 1.0 x 10-54 = 10^-54
3Pb2+(aq) + 9OH-(aq) →← 3Pb(OH)3-(aq) Keq = (8*10^13)^3 = 5.12*10^41
add all
Pb3(PO4)2(s) + 9OH-(aq) →← 3Pb(OH)3-(aq) + 2 PO43-(aq) Ktotal Keq1Keq2 = (10^-54)(5.12*10^41) =5.12*10^-13
then
K = [Pb(OH)3-]^3 * [PO4-3]^2 / [OH-]^9
pH = 10 ; pOH = 4, [OH-] = 10^-4
5.12*10^-13 = (3S)^3*(2S)^2 / (10^-4)^9
108*S^5 = (5.12*10^-13)((10^-4)^9)
S = ((5.12*10^-49)/(108))^(1/5)
S = 8.613*10^-11
[Pb(OH)3-] = 3S = 3* 8.613*10^-11 =2.583*10^-10 M
[PO4-3] = 2S = 2* 8.613*10^-11 = 1.722*10^-10